Geohazards VR: Amalgamating Virtual Reality towards Geological Risk Assessment Teaching - Leite, Silvio; Coura, Laura; Delabrida, Saul (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
Virtual reality (VR) technology offers a promising solution by providing an immersive and interactive learning experience. This research is developing a VR environment specifically to teach geological risk in the public schools, where traditional teaching methods often struggle to convey the complex concepts of risk assessment. The use of VR and gamification seems promising in order to engage students and promote knowledge retention, so Geohazards VR aims to teach about geological risk in a total immersive VR gamified environment. The game have several quests and missions where the student will gradually understand, acknowledge, evaluate and recognise geological risk phenomena with a given opportunity to mitigate it.